Single-nucleus RNA-sequencing reveals NRF1/NFE2L1 as a key factor determining the thermogenesis and cellular heterogeneity and dynamics of brown adipose tissues in mice - Wei Shen; Suping Ren; Yongyong Hou; Zhuo Zuo; Shengnan Liu; Zhiyuan Liu; Jingqi Fu; Huihui Wang; Bei Yang; Rui Zhao; Yanyan Chen; Masayuki Yamamoto; et al. (Redox Biology, 2023)
Brown adipose tissue (BAT) is a major site of non-shivering thermogenesis in mammals and plays an important role in energy homeostasis. Nuclear factor-erythroid 2-related factor 1 (NFE2L1, also known as Nrf1), a master regulator of cellular metabolic homeostasis and numerous stress responses, has been found to function as a critical driver in BAT thermogenic adaption to cold or obesity by providing proteometabolic quality control. Our recent studies using adipocyte-specific Nfe2l1 knockout [Nfe2l1(f)-KO] mice demonstrated that NFE2L1-dependent transcription of lipolytic genes is crucial for white adipose tissue (WAT) homeostasis and plasticity. In the present study, we found that Nfe2l1(f)-KO mice develop an age-dependent whitening and shrinking of BAT, with signatures of down-regulation of proteasome, impaired mitochondrial function, reduced thermogenesis, pro-inflammation, and elevated regulatory cell death (RCD). Mechanistic studies revealed that deficiency of Nfe2l1 in brown adipocytes (BAC) primarily results in down-regulation of lipolytic genes, which decelerates lipolysis, making BAC unable to fuel thermogenesis. These changes lead to BAC hypertrophy, inflammation-associated RCD, and consequently cold intolerance. Single-nucleus RNA-sequencing of BAT reveals that deficiency of Nfe2l1 induces significant transcriptomic changes leading to aberrant expression of a variety of genes involved in lipid metabolism, proteasome, mitochondrial stress, inflammatory responses, and inflammation-related RCD in distinct subpopulations of BAC. Taken together, our study demonstrated that NFE2L1 serves as a vital transcriptional regulator that controls the lipid metabolic homeostasis in BAC, which in turn determines the metabolic dynamics, cellular heterogeneity and subsequently cell fates in BAT.